De novo SCN1A missense variant in a patient with Parkinson’s disease - Alluqmani, Majed; Alayoubi, Abdulfatah M.; Hashmi, Jamil A.; Basit, Sulman (Frontiers in Genetics, 2024)
BackgroundVariants in a gene encoding sodium voltage-gated channel alpha subunit 1 (SCN1A) are known to cause a broad clinical spectrum of epilepsy and associated features, including Dravet syndrome (MIM 607208), non-Dravet developmental and epileptic encephalopathy (MIM 619317), familial febrile seizures (MIM 604403), familial hemiplegic migraine (MIM 609634), and generalized epilepsy with febrile seizures (MIM 604403).MethodsIn this study, we examined a patient with Parkinson’s disease (PD) without any clinical manifestations of epilepsy and associated features. Genomic nucleic acid was extracted, and a complete coding sequence of the human genome (whole-exome sequencing) was sequenced. Moreover, Sanger sequencing of variants of interest was performed to validate the exome-discovered variants.ResultsWe identified a heterozygous pathogenic missense mutation (c.1498C>T; p.Arg500Trp) in the SCN1A gene in the patient using the whole-exome sequencing approach. The onset of PD features in our patient occurred at the age of 30 years. Biochemical investigations were carried out to rule out any secondary cause of the disease, including Wilson's disease or another metabolic disorder. MRI of the brain and spinal images were unremarkable. Moreover, a dramatic response to carbidopa–levodopa treatment was also observed in the patient.ConclusionOur results suggest that the pathogenic variant in SCN1A may lead to PD features without epilepsy.